2023
DOI: 10.1029/2023gl104664
|View full text |Cite
|
Sign up to set email alerts
|

Local Infrasound Monitoring of Lava Eruptions at Nyiragongo Volcano (D.R. Congo) Using Urban and Near‐Source Stations

Julien Barrière,
Adrien Oth,
Nicolas d’Oreye
et al.

Abstract: During eruptions, volcanoes produce air‐pressure waves inaudible for the human ear called infrasound, which are very helpful for detecting early signs of magma at the surface. Compared to violent ash‐rich explosions, recording more discrete atmospheric disturbances from effusive eruptions remains a practical challenge depending on the distance to the source. At Nyiragongo volcano (D.R. Congo), towering above a 1‐million urban area, we analyzed local infrasonic records between January 2018 and April 2022. An ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Tracking seismic network coherence (Seydoux et al, 2016;Soubestre et al, 2018) has also shown considerable recent success in identifying tremor at several volcanic settings (Journeau et al, 2022;Maher et al, 2023). Acoustic tremor, on the other hand, has been primarily detected and monitored using array processing techniques (Bishop et al, 2020;Matoza et al, 2010), cross-correlation functions on locally deployed acoustic sensors (Barrière et al, 2023), or statistical tests on successive spectral windows (Luo et al, 2023). Ripepe et al (2007) also demonstrated the detection of acoustic tremor from Stromboli Volcano, Italy, using multi-channel semblance analyses (Ripepe & Marchetti, 2002), while Johnson and Palma (2015) used a combination of cross-correlation lag times and semblance analyses on array data to study infrasonic tremor from lahars at Volcán Villarrica, Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking seismic network coherence (Seydoux et al, 2016;Soubestre et al, 2018) has also shown considerable recent success in identifying tremor at several volcanic settings (Journeau et al, 2022;Maher et al, 2023). Acoustic tremor, on the other hand, has been primarily detected and monitored using array processing techniques (Bishop et al, 2020;Matoza et al, 2010), cross-correlation functions on locally deployed acoustic sensors (Barrière et al, 2023), or statistical tests on successive spectral windows (Luo et al, 2023). Ripepe et al (2007) also demonstrated the detection of acoustic tremor from Stromboli Volcano, Italy, using multi-channel semblance analyses (Ripepe & Marchetti, 2002), while Johnson and Palma (2015) used a combination of cross-correlation lag times and semblance analyses on array data to study infrasonic tremor from lahars at Volcán Villarrica, Chile.…”
Section: Introductionmentioning
confidence: 99%